Uma proposta de ensino de Física moderna e contemporânea para alunos com e sem deficiência visual - Souza, Bruno Eron Magalhães de (2016)
The present paper aims to contribute to the reflection about Special Education, when raising questions around a methodology which includes students with and without visual impairment in lessons of Physics. Therefore, this work discusses the importance of teaching topics of Modern and Contemporary Physics still in high school, and it presents a conceptual guide to the notions discussed during the application of the research project: Particle Physics and Nuclear Physics and Radioactivity, used as subsidy for professionals interested in applying a methodology which addresses these issues. The tactile-visual material employed in the application of this work is described and the materials are exposed with explanations about their construction. The material was designed in order to contemplate students either with or without visual impairment in lessons of Physics. This project was executed in a regular high school in the city of Fortaleza. Through the use of the historical-philosophical approach and the construct the specific materials to expose concepts of modern physics, it was expected that those who get involved in this application realize the importance and the presence of such concepts in their daily lives. Through the result of analysis, it can be observed a reflexive posture on the part of students either with or without visual impairment, on the theme of inclusion of students and the addressed physics topics, realizing an interest in the concepts and in the presented information and a reflection on the relationship between such issues, science in general and society